(untitled) (Praxis Educativa, 2025)
This article analyzes the conditions and didactic interventions that guide the operations of searching and selecting information in teaching socially relevant issues in Social Sciences classes in secondary education within the Metropolitan Area of Buenos Aires (AMBA). Data collection took place during 2022 and 2023, involving analysis of 98 surveys and 65 interviews selected through theoretical sampling from various public and private secondary education institutions across different geographical locations within AMBA. From a teaching perspective, cognitive gaps were identified in the practices of searching and selecting information that required differentiated teaching devices. It is concluded that it is necessary to expand didactic time dedicated to searching and selecting information on socially relevant issues, and the presence of hesitant and dialogical teaching interventions is essential for the construction of social knowledge.